ANALISIS PERBANDINGAN WATAK DAN WUJUD MORAL DALAM DONGENG ASCHENPUTTEL DAN ANDE-ANDE LUMUT - Aurelia Noer Aryaputri; Lucky Herliawan Yanuar Amalputra; Putrasulung Baginda (Jurusan Pendidikan Bahasa Jerman FPBS UPI, 2023)
This research was conducted to find out the similarities and differences between the fairy tales Aschenputtel and Ande-Ande Lumut, one of which is the character and moral lesson. The moral messages contained in the fairy tales can be used as lessons for life. The purpose of this study is to describe the moral messages and the similarities and differences between the fairy tales. The research method used is a descriptive qualitative method and an objective research approach with comparative literature method. The stages of data analysis in this research are collecting data that have similarities and differences, compiling data according to their types, and comparing them in tables, which are then described to draw conclusions based on the analyzed data. Based on the results of data analysis, it can be concluded that 1) The moral messages contained in Aschenputtel fairy tales are good and bad morals. 2) The moral messages contained in the Ande-Ande Lumut fairy tales are good and bad morals. 3) There are similarities and differences in characterization in both fairy tales. At the same time, there is a moral lesson in both fairy tales, namely the value of morality with oneself, with fellow human beings and with God. The difference in moral lesson lies in the value of morality towards nature. Based on the research results, analysis that the two fairy tales have differences in the intercultural aspects.